2014
DOI: 10.1104/pp.114.247866
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Alternative Oxidase Maintains Respiration and Preserves Photosynthetic Capacity during Moderate Drought in Nicotiana tabacum    

Abstract: The mitochondrial electron transport chain includes an alternative oxidase (AOX) that is hypothesized to aid photosynthetic metabolism, perhaps by acting as an additional electron sink for photogenerated reductant or by dampening the generation of reactive oxygen species. Gas exchange, chlorophyll fluorescence, photosystem I (PSI) absorbance, and biochemical and protein analyses were used to compare respiration and photosynthesis of Nicotiana tabacum 'Petit Havana SR1' wild-type plants with that of transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 96 publications
2
101
0
Order By: Relevance
“…The amount of ATP synthase will have an effect on the propensity for TPU. Water stress has been shown to reduce ATP synthase protein amount and to induce TPU (Tezara et al 1999;Kohzuma et al 2009;Dahal et al 2014). Thus, it appears when leaves experience low CO 2 , for example as a result of water stress, the capacity for TPU is rapidly reduced both by reducing starch and sucrose synthesis and reducing ATP synthase, leaving TPU capacity only slightly greater than likely to be needed.…”
Section: Tpu Is Normally In Slight Excess Of the Required Capacitymentioning
confidence: 97%
See 1 more Smart Citation
“…The amount of ATP synthase will have an effect on the propensity for TPU. Water stress has been shown to reduce ATP synthase protein amount and to induce TPU (Tezara et al 1999;Kohzuma et al 2009;Dahal et al 2014). Thus, it appears when leaves experience low CO 2 , for example as a result of water stress, the capacity for TPU is rapidly reduced both by reducing starch and sucrose synthesis and reducing ATP synthase, leaving TPU capacity only slightly greater than likely to be needed.…”
Section: Tpu Is Normally In Slight Excess Of the Required Capacitymentioning
confidence: 97%
“…TPU is at the interface between growth and physiology of the plant and the production of resources needed for growth. Dahal et al (2014) found that tobacco plants lacking alternative oxidase showed no propensity for TPU until water-stressed. Unstressed plants had identical responses of A to C i but after water stress a line overexpressing alternative oxidase showed no TPU limitation while WT exhibited a clear TPU limitation.…”
Section: Tpu Is Normally In Slight Excess Of the Required Capacitymentioning
confidence: 98%
“…Studies in Arabidopsis and tobacco (Nicotiana tabacum) clearly revealed a role for AOX in the dissipation of excessive reducing power while maintaining photosynthesis under high-light stress (Florez-Sarasa et al, 2011Dahal et al, 2014Dahal et al, , 2015Vanlerberghe et al, 2016). In Arabidopsis, aox1a knockout plants cannot be complemented by the expression of other isogenes (Strodtkötter et al, 2009;Kühn et al, 2015).…”
mentioning
confidence: 99%
“…For example, the glycosyltransferase UGT74E2 targets auxins and upon overexpression triggers profuse shoot branching and drought tolerance (Tognetti et al, 2010). Also, the classical mitochondrial stress marker gene alternative oxidase AOX1a was found to be important during osmotic stress (Dojcinovic et al, 2005;Dahal et al, 2014), and recently it was shown that the mitochondrial outer membrane ATPase AtOM66 (AtBCS1) is a regulator of cell death that controls pathogen resistance, senescence, and drought tolerance . Therefore, it is evident that energy organelle signaling is an important part of general stress responses, and understanding the way it is controlled could provide a means to enhance stress tolerance and, thus, productivity in crop species.…”
mentioning
confidence: 99%